2021
DOI: 10.1007/s40259-021-00487-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Infusion-Related Reactions Following Dosing of Reference Rituximab and PF-05280586, a Rituximab Biosimilar

Abstract: Background Infusion-related reactions (IRRs) are the most common adverse event (AE) associated with infusion of rituximab, an anti-CD20 monoclonal antibody. Objective Our objective was to evaluate the impact of dosing/infusion patterns and certain baseline characteristics on IRR occurrence during the first rituximab infusion administered as the biosimilar PF-05280586 (RTX-PF) or reference rituximab sourced from the EU (RTX-EU, MabThera ® ) in patients with CD20+ low-tumor-burden follicular lymphoma. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…In this two-cohort study based on the French National Health Data System, we did not show an increased risk of hypersensitivity reaction associated with the injection of rituximab biosimilar compared with rituximab originator, neither in an initiation or switch context, nor for the first injection or over time. This result is consistent with clinical trials [8][9][10]35], observational studies, and systematic reviews dealing with monoclonal antibodies or fusion proteins [36][37][38][39][40][41][42], in which the authors showed no difference between the biosimilar product and originator product in terms of safety and immunogenicity, and in particular regarding hypersensitivity reactions, at either initiation or switch [16,18,43]. However, these studies were small and thus could not detect the rare events we were able to study.…”
Section: Discussionsupporting
confidence: 85%
“…In this two-cohort study based on the French National Health Data System, we did not show an increased risk of hypersensitivity reaction associated with the injection of rituximab biosimilar compared with rituximab originator, neither in an initiation or switch context, nor for the first injection or over time. This result is consistent with clinical trials [8][9][10]35], observational studies, and systematic reviews dealing with monoclonal antibodies or fusion proteins [36][37][38][39][40][41][42], in which the authors showed no difference between the biosimilar product and originator product in terms of safety and immunogenicity, and in particular regarding hypersensitivity reactions, at either initiation or switch [16,18,43]. However, these studies were small and thus could not detect the rare events we were able to study.…”
Section: Discussionsupporting
confidence: 85%
“…This discrepancy may be due to the retrospective nature of this study, which may have resulted in the omission of some minor adverse events. In addition, the most common type of adverse reaction in previous studies was infusion reactions (7), which was relatively infrequent in the present study; this may have been due to the use of anti-allergy medication prior to infusion and the limited rate of infusion to avoid or ameliorate infusion-related events to some extent (32,33). For serious adverse events, relevant data were carefully verified in this study, and none of them were malignant or fatal.…”
Section: Discussionmentioning
confidence: 51%
“…주입관련반응 발생은 보통 주사의 주입속도, CD20+ B세포의 농도 와 관련되며 주사를 반복할수록 빈도가 감소하는 것으로 알려 져 있다 39. 스티븐스-존슨증후군, 독성표피괴사용해 등의 심한 반응은 약 10%에서 발생하는 것으로 알려져 있다 40,41.…”
unclassified